Students' perceptions of the use of artificial intelligence in educational services - Ines Djokic; Nikola Milićević; Nenad Djokic; Borka Malcic; Branimir Kalas (Amfiteatru Economic, 2024)
The increased significance of artificial intelligence (AI) and the possibilities to implement it in higher education can be identified in contemporary conditions. At the same time, one cannot neglect the importance of student perceptions regarding it, since they represent the final users of educational services. Therefore, the focus of this study was on the implementation of the already developed Student Conceptions of AI in Education Scale (SCAIES) instrument on a sample of Serbian students. It is the first implementation of that eight-factor instrument modelled as a reflective-formative hierarchical construct which can be considered as its main contribution from the theoretical aspect. Thus, all eight factors positively and significantly formed the use of AI in education (UAIEd) from students' perspective, whereas the largest contribution could be attributed to factors arising from weaknesses of traditional education, i.e. sentiment analysis in education, personalised learning and student performance prediction. On the other hand, the lowest contribution could be attributed to factors that could be related to privacy concerns about AI use and the domain of control, concretely, classroom monitoring and visual analysis, and students' grade and evaluation. Some general recommendations for higher education institutions were also provided.
Keywords: M31; I20; 330; Artificial intelligence; education; students; perceptions; services